PENYATUAN KALENDER ISLAM INTERNASIONAL: PERSPEKTIF SIYASAH - Iqbal, Muhammad (JURIS (Jurnal Ilmiah Syariah), 2016)
Moslems all over the world need a calendar which can be used internationally. In order to realize such a noble need, several efforts have been made by two popular approaches, namely hisab and rukyat in establishing Islamic calendar. In the context of international Islam, this trend has been followed up by efforts of uniting global Islamic calendar. This article aims at discussing advantages of uniting global Islamic calendar in terms of political issues. From the perspectives of Islamic political science (siyasah) it can be point out that the existence of global Islamic calendar  will convince the world concerning with the unity and solidarity of Islamic powers. Moslems countries will arrive at shared attitudes and responses toward the development of global issues, especially those concern with Islamic political purposes.